Analisis Strategi Retorika dan Kesantunan Berbahasa Siswa Kelas X MAN 2 Kota Bengkulu dalam Teks Negosiasi Berbasis Isu Lingkungan Sekolah - Farinda, Arin; Suradi, Ahmad; Putri Juni Astuti, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to qualitatively analyze and describe the rhetorical strategies and linguistic principles employed by 10th-grade students at MAN 2 Bengkulu City in composing written negotiation texts based on school environmental issues. Negotiation skills are an essential competency in Phase E of the Merdeka Curriculum, which integrates persuasive skills and language-based conflict management. The research approach used is qualitative, employing content analysis. The subjects of this study are 10th-grade students at MAN 2 Bengkulu City for the 2025/2026 academic year, selected through purposive sampling. Data collection was conducted through documentation of student negotiation text drafts in their portfolios, observation of text-drafting activities, and in-depth interviews with student representatives and Indonesian language teachers. Data validity was tested using methodological triangulation and data source triangulation. Data analysis was conducted using the interactive model proposed by Miles, Huberman, and Saldaña. The results of the study indicate that, in terms of rhetoric, students predominantly employed the logos strategy (logical appeal) by utilizing empirical facts from the school environment, followed by the pathos strategy (emotional appeal) to foster empathy, while the use of the ethos strategy (personal credibility) remained very limited. In terms of politeness in language use, students tend to adhere to the maxim of wisdom and the maxim of acceptance (the maxim of generosity) to minimize harm to their conversation partners. However, violations of the modesty maxim were also found due to the dominance of adolescent egos in defending their arguments. Internal factors, such as a limited formal vocabulary, and external factors, such as a lack of contextual practice, are the main obstacles students face in combining persuasive rhetoric with ideal politeness.